Growth, structural change and vulnerability in CARICOM countries - Ramsaran, Ramesh (2003)
Discusses the growth experience in CARICOM countries, the nature of structural change and weaknesses in the integration strategy. Looks at the prospects facing the region in the emerging global environment.